ANALISIS PENGGUNAAN APLIKASI MAXIM UNTUK MENINGKATKAN KUALITAS LAYANAN MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Liwandouw, Jannuar Gideon; Yunus, Arfan; Saharaeni, Yeni (KHARISMA Tech, 2024)
The purpose of this study is to analyze the use of the maxim application to improve service quality using the User Experience Questionnaire (UEQ). This study used the User Experience Questionnaire (UEQ) research method and in this study also collected questionnaire data and a total sample of 50 people. Sources of data in this study are primary and secondary data. With the stages of research starting from determining the formulation of the problem, analyzing needs, determining questions, determining respondents, measuring UEQ, and the last is drawing conclusions. The results of this study indicate that the service quality of the Maxim application still needs to be improved. This is supported by the results of the benchmark diagram where the average is in the yellow area which means below average and even red which means bad. Of the 6 existing aspects or scales, 3 aspects that are suggested to be updated or improved are attractiveness, accuracy, and novelty.